Political Corruption and the Nigerian Arabic Play: The Upper Class as a Case Study - Ameen , Basshir; Muhammed Sani, Muktar (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Corruption is a household nomenclature among mankind and despite its invisibility, it is felt in every sector of human society – politics, economics, governance, academics, health etc. Attempts to eradicate/reduce corruption have been made in different ways, including writing. “Upper Class” as a work of Art, is one of such writing, as it appraised political corruption. This paper therefore discussed the techniques adopted by the play “Upper Class” in eradicating political corruption in Funore, an imaginary Nigerian city. The political corruption in the play manifested in the behaviour of the aristocratic group who promote corruption in Funore city by giving bribes in many ways to install Prince Finafina as the king of the city at all cost. But Shaykh Abdul-Mu'eez Gomina and his followers in the league of Ulamau and Imams (Islamic Scholars) waged wars against them and every other act of corruption, as it was ensured that the Funore people maintained their rights and freedoms of choosing their leader. They achieved their aims with the readiness of the people, supports from the Police, Judges, as well as the Government. Adopting the descriptive method, the researcher explained how Prince corrupt strategies of Finafina and his allies failed and he was arrested for many atrocities he committed both at home and abroad, while Prince Udu was unanimously elected for the throne by the three chiefs of Funore. Finally, the findings of this study revealed that, if there is rule of law, our societies will be good, and corruption will diffidently be reduced.